2020
DOI: 10.2478/prilozi-2020-0018
|View full text |Cite
|
Sign up to set email alerts
|

Detection of TMPRSS2-ERG Fusion Transcript in Biopsy Specimen of Prostate Cancer Patients: A Single Centre Experience

Abstract: AbstractIntroduction: Prostate carcinoma is the most frequent malign neoplasm among men with an ever-growing incidence rate. TMPRSS2-ERG fusion transcript leads to the androgen induction of ERG proto-oncogenes expression, representing a high presence of oncogenes alteration among prostate tumour cells.Aim: The aim of this research was to detect and evaluate theTMPRSS2-ERG fuse transcript in the tissues of patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 59 publications
(62 reference statements)
0
4
0
Order By: Relevance
“…Previous studies of TMPRSS2 in cancer mainly focused on its oncogenic role in prostate cancer. [6][7][8] In this study, we focused on LUAD, considering that it is the most common histological type in lung cancer and that the lungs are the primary organ SARS-CoV-2 attacks. In contrast to its oncogenic role in prostate cancer, TMPRSS2 plays a tumor suppressive role in LUAD, as we have provided abundant evidence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies of TMPRSS2 in cancer mainly focused on its oncogenic role in prostate cancer. [6][7][8] In this study, we focused on LUAD, considering that it is the most common histological type in lung cancer and that the lungs are the primary organ SARS-CoV-2 attacks. In contrast to its oncogenic role in prostate cancer, TMPRSS2 plays a tumor suppressive role in LUAD, as we have provided abundant evidence.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5] Typically, the TMPRSS2-ERG gene fusion frequently occurs in prostate cancer and is associated with tumor progression. [6][7][8] In a recent study, 3 Katopodis et al revealed that TMPRSS2 was overexpressed in various cancers versus their normal tissues. In another study, 4 Kong et al explored TMPRSS2 expression in lung adenocarcinoma (LUAD) and lung squamous cell carcinoma (LUSC).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of TMPRSS2 in cancer mainly focused on its oncogenic role in prostate cancer [6][7][8]. In this study, we focused on LUAD, considering that it is the most common histological type in lung cancer and that the lungs are the primary organ SARS-CoV-2 attacks.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated the association between TMPRSS2 and cancer [2][3][4][5]. Typically, the TMPRSS2-ERG gene fusion frequently occurs in prostate cancer and is associated with tumor progression [6][7][8]. In a recent study [3], Katopodis et al revealed that TMPRSS2 was overexpressed in various cancers versus their normal tissues.…”
Section: Introductionmentioning
confidence: 99%